EFEITOS DAS ISOFLAVONAS DE SOJA SOBRE OS EPITÉLIOS MAMÁRIO E ENDOMETRIAL DE RATAS OOFORECTOMIZADAS. - Oliveira, Paula de Lourdes Lauande (2008)
Purpose: To investigate the effect of chronic treatment with soy isoflavones, orally, in breast and uterine tissue in rats of oophorectomized. Methodology: To evaluate the effect of isoflavones from soy in reproductive tissue, were used 40 rats of the species Rattus norvegicus, distributed in 04 groups: ISO-treated with isoflavones from soy (10 mg / kg); EP-treated with estrogen progestogen (0.5 mg / kg); OOFooforectomizadas and OS- simulated operation. After the proof of the regularity of the estrous cycle, the ISO groups of rats, EP, OOF were submitted to oophorectomy after three weeks of evidence of anoestrus, were treated with isoflavones (ISO) or estrogen combined (EP), orally, for 6 months. Animals OS and OOF received saline over the same period of time. There were certain stages of the frequency of the estrous cycle, the wet weight of the uterus and examine the histology of breast and uterine tissue. Results: After six months of treatment group had matured ISO vagina, where 88% of swabs tested were found during estrus. As for breast histology, the group presented ISO ductal atrophy and fibrosis peritubular. The analysis of the wet weight of the uterus showed that oophorectomy was able to reduce by 86.0% the weight of that body, whose reduction of the values was maintained after treatment with isoflavones from soy. The histology of the uterus of rats treated with isoflavones showed the endometrial proliferative with dense stroma. Conclusion: So the chronic use of soy isoflavones, is able to stimulate the maturation of the vaginal epithelium and endometrial in oophorectomized rats and maintain the atrophy in the mammary glands and reducing the wet weight of the uterus, caused by oophorectomy.